Simultaneous Digital Design and Additive Manufacture of Structures and Materials. Issue 1 (December 2018) - Boddeti, Narasimha; Ding, Zhen; Kaijima, Sawako; Maute, Kurt; Dunn, Martin
Abstract The integration of emerging technologies into a complete digital thread promises to disrupt design and manufacturing workflows throughout the value chain to enable efficiency and productivity transformation, while unlocking completely new design freedom. A particularly appealing aspect involves the simultaneous design and manufacture of the macroscale structural topology and material microstructure of a product. Here we demonstrate such a workflow that digitally integrates:design automation – conception and automation of a design problem based on multiscale topology optimization;material compilation – computational geometry algorithms that create spatially-variable, physically-realizable multimaterial microstructures; anddigital fabrication – fabrication of multiscale optimized components via voxel-based additive manufacturing with material jetting of multiple photo-curable polymers. We validate the digital design and manufacturing workflow by designing, fabricating, and testing a series of structures that illustrate capabilities, show how it empowers the exploitation of new design freedom, and even challenges traditional design principles relating form, structure, and function.